Dissecting the variation of a visual trait: the proximate basis of UV‐Visible reflectance in crab spiders (Thomisidae). (3rd July 2014) - Gawryszewski, Felipe M.; Birch, Debra; Kemp, Darrell J.; Herberstein, Marie E.
Summary: The astounding diversity of animal coloration is indicative of a wide variety of selection pressures. Despite great interest in adaptive function, detailed understanding of the constituent elements of colour traits is lacking for many systems. Such information is important in allowing more accurate appraisals of colour variation and its potential production costs. In this study, we 'dissect' the dorsal colour of crab spiders (Thomisidae) to examine the mechanistic basis of a polyphenic colour trait. These spiders possess the ability to alter reflectance in the ultraviolet (UV), violet and blue wavelengths, changing their colour within days. We investigate and compare the proximate mechanistic basis of colour production in multiple phenotypes of three species using histology and spectrophotometry. Our analyses indicate that the spider cuticle is not equivalently transparent to light across the spectrum (300–700 nm) – as previously argued – and contributes to colour variation. UV light is reflected from guanine crystals, present in storage cells ventral to the hypodermis. The crystals are exposed through a partially UV‐transmitting hypodermis and cuticle. Variation from white to yellow is likely mediated through pigments/crystals present in different oxidative stages in the hypodermal cells. Simple mechanistic changes are therefore necessary to produce the observed variation, and likely underlie the evolutionary and ontogenetic lability of this trait. Our findings imply that either a UV‐reflective abdomen was the ancestral state for crab spiders, or, if pre‐dated by UV‐absorbent hypodermal pigments, the evolution of UV reflection has only involved the exposure of underlying guanine crystals through an otherwise clear hypodermis. Abstract : Lay Summary